CARREIRAS, José Albuquerque, MADURO, António Valério e RASQUILHO, Rui (coords.), Cister. Tomo I. Património e Arte - Barreira, Catarina Alexandra Martins Fernandes (2022)
UIDB/00749/2020 UIDP/00749/2020